The Use of Remotely Sensed Information within a Flood Risk Management and Analysis Tool (GARI) - Chokmani, Karem; Oubennaceur, Khalid; Tanguy, Marion; Poulin, Jimmy; Gauthier, Yves; Latapie, Romain; Bernier, Monique (IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium, 2019)
Floods are the most common natural hazard worldwide. GARI is a flood risk management and analysis tool that is being developed by the Environmental and Nordic Remote Sensing Group (TENOR) of INRS in Quebec City (Canada). Beyond mapping the flooded areas and water levels, GARI allows for the estimation, analysis and visualization of flood risks for individuals, residential buildings, and population. Information can therefore be used during the different phases of flood risk management. In the operational phase, GARI can use satellite radar images to map in near real-time the flooded areas and water levels. It uses an innovative approach that combines Radarsat-2 and hydraulic data, specifically flood return period data. Information from the GARI enable municipalities and individuals to anticipate the impacts of a flood in a given area, to mitigate these impacts, to prepare, and to better coordinate their actions during a flood.

Seasonal Variation of the Physico-chemical Composition of Ottawa River Waters in the St. Lawrence River - Frenette, Jean-Jacques; Assani, Ali A. (2018)
The goal of this study is to compare the seasonal variability of 12 physicochemical characteristics of waters in the Ottawa and St. Lawrence Rivers (SLR). Water samples were collected on board the research vessel Lampsillis in the spring (May), summer (August), and fall (October) of 2006 at four stations located downstream from the confluence of the two rivers. Temperature and total nitrogen values varied significantly for the three seasons. In contrast, seasonal values of light extinction coefficient and turbidity do not show any significant variation. The values of the other characteristics varied significantly only for one season. Comparison of these data with those measured in 1994–1996 reveals a net warming of the waters and a significant increase in nitrite-nitrate concentrations due to the increasing use of nitrogen-bearing fertilizers by farmers in Quebec. Concentrations of these two substances are higher than the limits set by the government of Quebec for water quality in rivers.

Groundwater contribution to river flows – using hydrograph separation, hydrological and hydrogeological models in a southern Quebec aquifer - Larocque, M.; Fortin, V.; Pharand, M. C.; Rivard, C. (Groundwater hydrology/Modelling approaches, 2010)
Abstract. Groundwater contribution to river flows, generally called base flows, often accounts for a significant proportion of total flow rate, especially during the dry season. The objective of this work is to test simple approaches requiring limited data to understand groundwater contribution to river flows. The Noire river basin in southern Quebec is used as a case study. A lumped conceptual hydrological model (the MOHYSE model), a groundwater flow model (MODFLOW) and hydrograph separation are used to provide estimates of base flow for the study area. Results show that the methods are complementary. Hydrograph separation and the MOHYSE surface flow model provide similar annual estimates for the groundwater contribution to river flow, but monthly base flows can vary significantly between the two methods. Both methods have the advantage of being easily implemented. However, the distinction between aquifer contribution and shallow subsurface contribution to base flow can only be made with a groundwater flow model. The aquifer renewal rate estimated with the MODFLOW model for the Noire River is 30% of the recharge estimated from base flow values. This is a significantly difference which can be crucial for regional-scale water management.
Keywords: Ouvrage_Collectif_Numéro1

Étude des facteurs contrôlant la présence de l’algue Didymosphenia geminata et des impacts de sa présence sur le saumon atlantique juvénile. - Gillis, Carole-Anne (Université du Québec, Institut national de la recherche scientifique, 2018)
L’algue Didymosphenia geminata est une diatomée à potentiel envahissant. Cette algue microscopique, attachée au substrat, peut sécréter des quantités phénoménales de mucilage et créer de vaste amas fibreux tapissant le lit d’une rivière. Autrefois considérée très rare et représentative d’une qualité d’eau impeccable, elle est maintenant répertoriée omniprésente dans les rivières oligotrophes à travers le monde. Au cours des deux dernières décennies, son émergence a créé un intérêt marqué de la part des écologistes et gestionnaires de rivières puisque sa biologie et les facteurs régissant son occurrence et sa sévérité sont méconnus. Au Québec, c’est à l’été 2006 que les premières proliférations massives de l’algue didymo ont été observées dans la rivière Matapédia. Le manque de connaissances à son égard, plus précisément sur sa distribution, les causes de l’apparition des proliférations et de l’impact négatif possible de cet envahissement sur le réseau trophique mais surtout sur le cycle de vie du saumon atlantique en rivière a créé un état de panique chez les gestionnaires et les utilisateurs des rivières à saumon. Il existait dès lors un urgent besoin de combler ces lacunes. Afin de mieux comprendre les facteurs régissant tant la croissance cellulaire que la croissance des amas mucilagineux, un modèle conceptuel a été élaboré grâce à la collaboration de plusieurs chercheurs travaillant au Colorado, à l’île de Vancouver, en Nouvelle-Zélande et au Québec afin de colliger les observations et les données de terrain. Ce travail de synthèse a permis d’identifier les facteurs favorisant sa colonisation, sa croissance et sa persistance en rivière. La dynamique spatio-temporelle de l’algue didymo est dépendante de divers facteurs (ou conditions environnementales) dont les seuils critiques déterminent son comportement de prolifération. En rivière, la croissance d’algues benthiques est principalement déterminée par les variations saisonnières du débit, la température, la lumière et la chimie de l’eau. Ainsi, la connaissance des paramètres d’habitats favorables permet de déterminer si un bassin versant est favorable à la présence cellulaire de l’algue didymo et à la probabilité que celle-ci puisse y proliférer. Le modèle conceptuel permet d’établir la variabilité et la sévérité saisonnière du comportement envahissant de l’algue didymo en rivière. Afin d’appliquer le modèle conceptuel développé à l’échelle du bassin versant, nous avons mis sur pied un réseau de suivi volontaire des proliférations d’algue didymo dans le bassin versant de la rivière Restigouche. Vingt-deux organisations différentes totalisant 70 bénévoles ont été formés à identifier et quantifier les proliférations d’algue didymo. Entre 2010 et 2015, 1 228 observations ont été réalisées. L’analyse de cette base de données, nous a permis de déterminer que 71% de la variabilité de la sévérité des proliférations durant l’été est inversement proportionnelle à l’intensité de la crue printanière. À l’échelle du tronçon, l’analyse des proliférations pour différents types de faciès-substrat a permis de d’identifier une préférence accrue pour les seuils. Par la suite, afin d’appliquer le modèle conceptuel à l’échelle régionale, nous avons comparé la distribution de l’algue didymo dans trois régions de l’est du Québec (i.e. Gaspésie, Bas-St-Laurent et Côte-Nord) avec divers paramètres physico-chimiques de vingt-neuf rivières à saumon. Le principal facteur régissant la présence-absence de cellules est le pH. Les diatomées ont des optimums de pH très spécifiques et la géologie contrastante de la Côte-Nord (Bouclier canadien) par rapport aux basses terres du Saint-Laurent et les Appalaches en Gaspésie, a permis d’identifier que les eaux acides riches en tanins et lignines ne sont pas favorables à la survie et la croissance de l’algue didymo. Grâce à une meilleure connaissance des facteurs de contrôle de l’algue didymo à diverses échelles spatiales, nous pouvons déterminer les rivières à risque de proliférations massives. Au sein des rivières exhibant des proliférations, nous avons déterminé que les préférences d’habitat de l’algue didymo sont identiques à celles du saumon atlantique juvénile (i.e. eaux rapides, peu profondes, claires, froides, faible en nutriments avec un substrat grossier). Afin de déterminer l’ampleur de l’impact de la présence des proliférations sur le réseau trophique, nous avons vérifié son impact sur la communauté algale. La structure dense et fibreuse crée un environnement physique dans lequel plusieurs diatomées peuvent s’y loger. Nos résultats confirment que l’algue crée un habitat de choix pour les plus petites diatomées favorisant ainsi une plus grande diversité taxonomique. Malgré une augmentation de la complexité du biofilm suivant son épaississement, il n’y a pas d’impact supplémentaire sur la structure et la diversité taxonomique des échantillons. Puisque la structure de l’habitat est modifiée par les tapis et que ces derniers sont susceptibles d’altérer la structure et le fonctionnement de l’écosystème, nous avons évalué l’effet des proliférations sur le comportement alimentaire des saumons juvéniles. Grâce à l’observation en apnée du comportement, nous pouvons conclure que les saumons juvéniles effectuent une plus grande proportion de quêtes benthiques en fonction du pourcentage de recouvrement algal. Ce changement de comportement n’est pas attribuable à une diminution des proies disponibles au sein de la dérive. Notre étude confirme la grande plasticité comportementale des saumons juvéniles face aux modifications de l’habitat. Afin de vérifier l’impact des proliférations sur les ressources alimentaires et la diète des saumons juvéniles, nous avons utilisé l’approche par analyse d’isotopes stables. Cette approche permet d’établir un portrait intégré de l’utilisation des ressources par les poissons. Les signatures isotopiques divergentes entre les différents tissus des saumons confirment une modification de la diète saisonnière. Les saumons juvéniles en présence de l’algue didymo ont une diète moins diversifiée et appauvrie en carbone principalement composée de petits chironomides et de trichoptères. Malgré que l’indice de condition physique des saumons juvéniles soit similaire entre les deux sites, leur taille est plus petite dans le site avec proliférations. Les travaux futurs devront tenter de valider l’impact de la diminution de la qualité de la diète par les proliférations d’algue didymo sur le contenu en lipides des juvéniles. Suite aux diverses collaborations internationales et discussions avec les gestionnaires, nous nous sommes rendus à l’évidence qu’il devait y avoir une recommandation sur les mesures de gestion vis-à-vis cette espèce. En fonction des connaissances scientifiques développées au fil des ans et plusieurs cas de gestion dans divers pays, nous avons recommandé aux gestionnaires d’éduquer les utilisateurs à vérifier, nettoyer, sécher et congeler leurs équipements. Que l’algue didymo soit une espèce exotique ou indigène, elle peut être propagée. De plus, la mise en valeur des saines pratiques permettent de limiter la propagation d’autres organismes pouvant potentiellement être plus dévastateurs que l’algue didymo. Les résultats de cette thèse contribuent à l’avancement des connaissances sur les facteurs de contrôle de l’algue didymo tant à l’échelle microscopique que macroscopique. En plus d’avoir contribué à élaborer le modèle conceptuel, nous l’avons amélioré en l’appliquant à diverses échelles spatiales : à l’échelle du tronçon et du bassin versant ainsi qu’à l’échelle régionale. C’est d’ailleurs la première étude à élaborer un réseau de suivi des proliférations par l’implication des acteurs du milieu ainsi qu’une des seules études à avoir examiné la variabilité interannuelle sur une période de six ans. C’est également la première étude à avoir évalué l’impact de l’algue didymo sur les communautés périphytiques dans l’est du Canada. De surcroît, c’est la première étude exhaustive qui a évalué l’effet des proliférations sur l’écologie du saumon atlantique juvénile. Les recherches menées sur le comportement alimentaire est également novateur et contribue considérablement à la compréhension des mécanismes et les interactions entre les divers niveaux trophiques et l’impact sur les salmonidés. Didymosphenia geminata is mat-forming nuisance diatom. This epilithic microscopic alga can secrete copious amounts of mucilage creating thick and extensive mats covering the entire riverbed. Once considered very rare and representative of pristine water quality, it is now ubiquitous in rivers around the world. Over the past two decades, this alga has emerged as a nuisance diatom and generated much interest among freshwater ecologists and river managers alike. Nonetheless, controlling factors governing the occurrence and severity of D. geminata are still not well understood. In Quebec, the first massive proliferations of D. geminata were reported in 2006 in the Matapedia River. There was an urgency to fill this knowledge gap as managers and government agencies panicked at the lack of knowledge regarding its distribution, the causes of its onset and mostly, fear of that this alga would act as an additional stressor to Atlantic salmon populations. To better understand controlling factors of both cell division and mat formation, a conceptual model was developed with the collaboration of several researchers working in Colorado, Vancouver Island, New Zealand and Quebec to collate observations and field data. This synthesis work helped identify the factors favoring its colonization, growth and persistence in rivers. The spatiotemporal dynamics of D. geminata are dependent on various dynamic thresholds of flow, temperature, light and water chemistry within the habitat window. We can therefore test various arrays of these parameters to determine whether rivers are likely to present occasional to persistent D. geminata mats. To test and improve upon the conceptual model at various spatial scales, we developed a monitoring network for D. geminata mat presence. Twenty-two different organizations totaling 70 volunteers were trained to identify and quantify the proliferations of D. geminata. Between 2010 and 2015, 1 228 observations were made. The analysis of this database helped determine that 71% of the variability of D. geminata severity is inversely proportional to the intensity of the spring flood. At the reach scale, habitat type was determinant for presence-absence of mats with a strong significant preference for riffles. At the provincial scale, we compared the distribution of D. geminata in three regions of eastern Quebec (i.e. Gaspesie, Bas-St-Laurent and Cote-Nord) against numerous water chemistry parameters for twentynine rivers. At the broad regional scale, pH was the most important factor governing the presence-absence of cells. Diatoms have very specific pH optima and the contrasting geologies between regions confirmed that low pH and high tannins and lignin are not favorable to the survival and growth of D. geminata. Habitat preferences for D. geminata mats are identical to those of juvenile Atlantic salmon (i.e. shallow, fast, clear, cool, low nutrient and coarse substrate). To determine the extent of the impact of the presence of mats on the food web, we verified its impact on the algal community. The dense interwoven matrix creates a suitable physical environment for small diatoms, thus promoting greater taxonomic diversity. Despite an increase in the complexity of the biofilm with mat accrual, there is no additional impact on the structure and taxonomic diversity of the samples. D. geminata effects to higher trophic levels have been suspected since the structure of the habitat is modified and could alter the structure and functioning of the ecosystem. We studied the foraging behaviour of juvenile Atlantic salmon in contrasting D. geminata severities. With increasing percent cover of the alga, juvenile Atlantic salmon switch from a drift-foray to benthic-foray strategy. This change in behavior is not due to limited drifting prey availability. Our results reinforce the notion that juvenile Atlantic salmon have high behavioral plasticity in response to habitat changes. To test the impact of mats on juvenile salmon diet, we used a stable isotope analysis approach. This approach provides an integrated view of resource use by fish. Contrasting isotopic signatures between the liver and muscle tissues confirm a change in the seasonal diet. Juvenile salmon sampled in the D. geminata impacted site have a less diversified and carbon-depleted diet composed mainly of small chironomids and Trichoptera. Juvenile salmon condition factors and C:N ratios were not different between sites, though their size is smaller in the impacted site. Future work should focus on the effects of reduced prey quality on lipid content of fish. Over various international collaborations and discussions with managers, it became clear that there was a need for a clear and standardized recommendation on management measures for this nuisance species. Based on recent scientific knowledge and several management cases in various countries, we recommended that managers educate users to check, clean, dry and freeze their equipment. Regardless of whether D. geminata is an exotic or native species, it can be spread. In addition, the development of best practices limits the spread of aquatic organisms as others may be far more devastating than D. geminata. The results of this thesis contribute to the advancement of knowledge on the controlling factors of D. geminata for both cells and mats. In addition to contributing to the development of the conceptual model, we have tested and improved it by applying it to a variety of spatial scales: at the reach, watershed and regional scales. This is the first study to develop a monitoring network for mat severity with the involvement of local stakeholders. It is also the first study to evaluate the impact of D. geminata on periphytic communities in eastern Canada. Moreover, it is the first comprehensive study that has evaluated the effect D. geminata mats on juvenile Atlantic salmon ecology. Research on foraging behavior is also innovative and contributes significantly to the understanding of the mechanisms and interactions by which D. geminata impacts various trophic levels and salmonids.

Suivi en temps réel de l’aléa inondation par cameras de surveillance : estimation du niveau de l’eau. - Latapie, Romain (Université du Québec, Institut national de la recherche scientifique, 2018)
Les inondations constituent l’un des risques naturels les plus fréquents. Une inondation historique survenue au Québec s’est produite aux abords de la rivière Richelieu entre avril et juin 2011. Suite aux dommages et aux frais occasionnés par cet épisode, l’INRS s’est engagé avec la ville de Saint-Jean-sur-Richelieu afin de la doter d’un système de Gestion et d’Analyse du Risque d’Inondation (GARI) : le niveau d’eau constitue une donnée essentielle pour l’évaluation de l’ampleur d’une inondation en temps réel. Ce travail de recherche a pour objectif de détecter automatiquement la ligne d’eau sur des images acquises par des caméras placées aux abords de la rivière Richelieu par des méthodes d’analyse d’images et de convertir cette dernière en niveau d’eau par stéréoscopie (transfert des valeurs en pixels en unité métrique). Le premier volet de ce travail de recherche s’intéresse à l’extraction automatique de la ligne d’eau à partir de données acquises par des caméras de surveillance. Afin de répondre à cette exigence, des séquences d’images de durée déterminée (une minute) ont été enregistrées et une image moyenne a été calculée pour chaque séquence. L’image moyenne est ensuite segmentée puis classifiée à l’aide d’une technique supervisée. Pour la première séquence d’images à traiter, des sites d’entraînement décrivant les parties immergées et libres sont créées afin d’obtenir deux classes de sortie correspondant aux surfaces d’eau et au reste de l’image. Une détection de contour permet d’isoler les pixels de la ligne d’eau. Pour les séquences suivantes, l’algorithme utilise automatiquement la ligne d’eau créée à la séquence précédente pour définir les sites d’entraînements à la séquence considérée. Le taux de réussite d’extraction de la ligne d’eau avoisine 90%. Le second volet consiste à convertir les coordonnées des pixels de la ligne d’eau du système bidimensionnel image vers un système tridimensionnel dans un référentiel connu. Les observations par stéréoscopie permettent cette transformation via les procédures d’orientation intérieure des caméras et d’orientation extérieure des couples stéréoscopiques. Pour le modèle de caméra considéré, les tests effectués montrent que les erreurs de positionnement planimétrique de la ligne d’eau sont inférieures au mètre et l’erreur de positionnement altimétrique (niveau d’eau) est inférieure à 10 cm lorsque le rapport entre la base stéréoscopique et la distance avec l’objet à modéliser est supérieur à 0.1. Flooding is one of the most common natural hazards. A historic flood occurred in the vicinity of the Richelieu River (Province of Quebec, Canada) between April and June 2011. After the damages and expenses incurred by this episode, INRS and the city of Saint-Jean-sur-Richelieu decided to create a flood risk management and analysis system : water level is an essential factor for assessing magnitude of a flood in real time. This research project aims to automatically detect the water line on images acquired by cameras located near the Richelieu River with image analysis methods and to convert it to water level by stereoscopy (transfer of values from pixel unit to metric unit). The first part of this research work focuses on automatic extraction of water line from data acquired by surveillance cameras. In order to meet this requirement, fixed-duration (one minute) image sequences were recorded and an average image was calculated for each sequence. Average image is then segmented and classified using a supervised technique. For the first sequence of images to be processed, training sites describing submerged and free portions are created to obtain two output classes corresponding to water and the rest of the image. Then, a contour detection is used to determine water line. For the following sequences, the algorithm automatically uses water line created in the previous sequence to define training sites for the present sequence. Success rate of water line extraction is around 90%. Second part consists in converting pixels coordinates of water line known in a two-dimensional image system to a three-dimensional system in a known reference frame. Stereoscopic observations allow this transformation via interior and exterior orientations procedures. For the camera model considered in this project, tests highlight that planimetric positioning errors of the water line are lower than 1 m and altimetric positioning error (water level) is lower than 10 cm when the ratio between stereoscopic basis and distance to the object to be modeled is higher than 0.1.

Development of a methodology to assess future trends in low flows at the watershed scale using solely climate data - Foulon, Étienne; Rousseau, Alain N.; Gagnon, Patrick (Journal of Hydrology, 2018)
Abstract Low flow conditions are governed by short-to-medium term weather conditions or long term climate conditions. This prompts the question: given climate scenarios, is it possible to assess future extreme low flow conditions from climate data indices (CDIs)? Or should we rely on the conventional approach of using outputs of climate models as inputs to a hydrological model? Several CDIs were computed using 42 climate scenarios over the years 1961–2100 for two watersheds located in Quebec, Canada. The relationship between the CDIs and hydrological data indices (HDIs; 7- and 30-day low flows for two hydrological seasons) were examined through correlation analysis to identify the indices governing low flows. Results of the Mann-Kendall test, with a modification for autocorrelated data, clearly identified trends. A partial correlation analysis allowed attributing the observed trends in HDIs to trends in specific CDIs. Furthermore, results showed that, even during the spatial validation process, the methodological framework was able to assess trends in low flow series from: (i) trends in the effective drought index (EDI) computed from rainfall plus snowmelt minus PET amounts over ten to twelve months of the hydrological snow cover season or (ii) the cumulative difference between rainfall and potential evapotranspiration over five months of the snow free season. For 80% of the climate scenarios, trends in HDIs were successfully attributed to trends in CDIs. Overall, this paper introduces an efficient methodological framework to assess future trends in low flows given climate scenarios. The outcome may prove useful to municipalities concerned with source water management under changing climate conditions.
Keywords: Rousseau_Alain

Assessing the long-term hydrological services provided by wetlands under changing climate conditions: A case study approach of a Canadian watershed - Fossey, Maxime; Rousseau, Alain N. (Journal of Hydrology, 2016)
The water content of wetlands represents a key driver of their hydrological services and it is highly dependent on short- and long-term weather conditions, which will change, to some extent, under evolving climate conditions. The impact on stream flows of this critical dynamic component of wetlands remains poorly studied. While hydrodynamic modelling provide a framework to describe the functioning of individual wetland, hydrological modelling offers the opportunity to assess their services at the watershed scale with respect to their type (i.e., isolated or riparian). This study uses a novel approach combining hydrological modelling and limited field monitoring, to explore the effectiveness of wetlands under changing climate conditions. To achieve this, two isolated wetlands and two riparian wetlands, located in the Becancour River watershed within the St Lawrence Lowlands (Quebec, Canada), were monitored using piezometers and stable water isotopes (δD – δ18O) between October 2013 and October 2014. For the watershed hydrology component of this study, reference (1986–2015) and future meteorological data (2041–2070) were used as inputs to the PHYSITEL/HYDROTEL modelling platform. Results obtained from in-situ data illustrate singular hydrological dynamics for each typology of wetlands (i.e., isolated and riparian) and support the hydrological modelling approach used in this study. Meanwhile, simulation results indicate that climate change could affect differently the hydrological dynamics of wetlands and associated services (e.g., storage and slow release of water), including their seasonal contribution (i.e., flood mitigation and low flow support) according to each wetland typology. The methodological framework proposed in this paper meets the requirements of a functional tool capable of anticipating hydrological changes in wetlands at both the land management scale and the watershed management scale. Accordingly, this framework represents a starting point towards the design of effective wetland conservation and/or restoration programs.
Keywords: Rousseau_Alain

Integrated assessment of climate change impact on surface runoff contamination by pesticides - Gagnon, Patrick; Sheedy, Claudia; Rousseau, Alain N.; Bourgeois, Gaétan; Chouinard, Gérald (Integrated Environmental Assessment and Management, 2016)
Pesticide transport by surface runoff depends on climate, agricultural practices, topography, soil characteristics, crop type, and pest phenology. To accurately assess the impact of climate change, these factors must be accounted for in a single framework by integrating their interaction and uncertainty. This paper presents the development and application of a framework to assess the impact of climate change on pesticide transport by surface runoff in southern Quebec (Canada) for the 1981-2040 period. The crop enemies investigated were: weeds for corn (Zea mays); and for apple orchard (Malus pumila), three insect pests (codling moth (Cydia pomonella), plum curculio (Conotrachelus nenuphar) and apple maggot (Rhagoletis pomonella)) and two diseases (apple scab (Venturia inaequalis) and fire blight (Erwinia amylovora)). A total of 23 climate simulations, 19 sites, and 11 active ingredients were considered. The relationship between climate and phenology was accounted for by bioclimatic models of the Computer Centre for Agricultural Pest Forecasting (CIPRA) software. Exported loads of pesticides were evaluated at the edge-of-field scale using the Pesticide Root Zone Model (PRZM), simulating both hydrology and chemical transport. A stochastic model was developed to account for PRZM parameter uncertainty. Results of this study indicate that for the 2011-2040 period, application dates would be advanced from 3 to 7 days on average with respect to the 1981-2010 period. However, the impact of climate change on maximum daily rainfall during the application window is not statistically significant, mainly due to the high variability of extreme rainfall events. Hence for the studied sites and crop enemies considered, climate change impact on pesticide transported in surface runoff is not statistically significant throughout the 2011-2040 period.
Keywords: Rousseau_Alain

Dynamics of groundwater floodwaves and groundwater flood events in an alluvial aquifer - Buffin-Bélanger, Thomas; Cloutier, Claude-André; Tremblay, Catherine; Chaillou, Gwénaëlle; Larocque, Marie (2016)
In gravelly floodplains, streamflood events induce groundwater floodwaves that propagate through the alluvial aquifer. Understanding groundwater floodwave dynamics can contribute to groundwater ﬂood risk management. This study documents groundwater floodwaves on a flood event basis to fully assess environmental factors that control their propagation velocity, their amplitude and their extension in the floodplain, and examines the expression of groundwater flooding in the Matane River floodplain (Quebec, Canada). An array of 15 piezometers equipped with automated level sensors and a river stage gauge monitoring at 15-minute intervals from September 2011 to September 2014 were installed within a 0.04-km2 area of the floodplain. Cross-correlation analyses were performed between piezometric and river-level time series for 54 flood events. The results reveal that groundwater floodwave propagation occurs at all flood magnitudes. The smaller floods produced a clear groundwater floodwave through the floodplain, while the largest floods affected local groundwater flow orientation by generating an inversion of the hydraulic gradient. Propagation velocities ranging from 8 to 13 m/h, which are two to three orders of magnitude higher than groundwater velocity, were documented while the induced pulse propagated across the floodplain to more than 230 m from the channel. Propagation velocity and amplitude attenuation of the groundwater floodwaves depend both on flood event characteristics and the aquifer characteristics. Groundwater flooding events are documented at discharge below bankfull (< 0.5 Qbf). This study highlights the role of flood event hydrographs and environmental variables on groundwater floodwave properties and the complex relationship between flood event discharge and groundwater flooding. The role that groundwater floodwaves play in flood mapping and the ability of analytical solutions to reproduce them are also discussed.

Combining streamflow observations and hydrologic simulations for the retrospective estimation of daily streamflow for ungauged rivers in southern Quebec (Canada) - Lachance-Cloutier, Simon; Turcotte, Richard; Cyr, Jean-François (Journal of Hydrology, 2017)
Abstract Retrospective estimation of daily streamflow for all rivers within a territory is of practical interest for sustainable and optimal water management. This implies, however, the availability of methods for providing accurate estimations of flow for ungauged rivers. This study compares the potential of statistical interpolation (SI)—a simple data assimilation technique that combines observations and simulations from hydrological modelling—with four other approaches: nearest neighbour, direct use of outputs from hydrological modelling, ordinary and topological kriging. Through subsampling cross-validation analyses based on the modified Kling-Gupta efficiency indicator, we show that SI compares favourably with these other approaches. While the performance of other methods depends on the configuration of the ungauged site in regards to the neighbouring reference sites, SI is less affected by these configurations. SI outperforms the other approaches particularly where the ungauged site is relatively distant from observation sites. In these cases, SI performance depends on the performance of the background model that relies on simulations of hydrological processes forced by precipitation and temperature observations. Our findings offer the potential for heightened performance estimates through an improvement of hydrological modelling and the use of more complex assimilation techniques for exploiting the model.

La réduction des risques de désastres : défis et possibilités pour le Québec et le Canada. Université du Québec à Montréal, Chaire de recherche UQAM sur les risques hydrométéorologiques liés aux changements climatiques - Boyer-Villemaire, U.; Gachon, P.; Boucher, E.; Germain, D.; Raphoz, M.; Doré, M. C.; Martin, J. P. (2017)
En marge de la Cinquième Plateforme régionale pour la Réduction des risques de catastrophes des Amériques (PRA), le gouvernement du Canada a approché l’Institut des sciences de l’environnement(ISE) de l’Université du Québec à Montréal(UQAM) afin d’organiser un forum public. Les échanges de ce dernier devaient servir à alimenter les discussions de la PRA. Au total, 21 experts ont discuté avec une centaine de participants lors de panels organisés à l’UQAM sous les thèmes de la santé, de la sécurité civile et de l’aménagement du territoire. Plusieurs thèmes transversaux ont aussi émergé tout au long du forum. Il importe de pérenniser le rôle de la recherche et d’améliorer les capacités de formation technique et universitaire afin de former des spécialistes en mesure d’appréhender la complexité de la gestion du risque dans un contexte de changements environnementaux et climatiques. Ceci est également essentiel pour l’identification des facteurs de risque (multisources ou multidimensionnels), pour tirer des leçons apprises des événements majeurs passés et récents, et pour développer ou mettre à jour la connaissance sur les tendances en cours et à venir des aléas météorologiques, ainsi que des facteurs de vulnérabilité et d’exposition. Tous les panels ont discuté de l’importance de favoriser le décloisonnement intra/interorganisationnel pour promouvoir la transsectorialité et les retours d’expériences systématiques. Pour ce faire, il faut s’inspirer des modèles internationaux, notamment du système d’alertes hydrométéorologiques présenté par Météo-France. Celui-ci inclut une vigilance météorologique qui cible des populations et des autorités publiques, et les informe des comportements et des règles à suivre lors d’alertes plus problématiques (vigilance aux stades orange et rouge). Finalement, l’amélioration de la communication et le libre accès à l’information sont des éléments essentiels pour protéger les individus et développer une société plus résiliente.
Keywords: Gachon_Philippe

Entre attachement aux lieux et gestion de la reconstruction post-sinistre : l’action municipale au centre-ville de Lac-Mégantic, Québec (Canada) - Bouchard-Bastien, Emmanuelle; Brisson, Geneviève (Norois, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Climate Change Impacts on Catchment Hydrology in Eastern Canada - Aygün, O.; Kinnard, C.; Campeau, S. (2019)
Snowmelt dominated regions are receiving increasing attention due to their noticeably rapid response to ongoing climate change, which raises concerns about the altered hydrological risks under climate change scenarios. This study aims to assess the climate change impacts on hydrology over two contrasted catchments in southern Québec: Acadie River and Montmorency River catchments. These river catchments represent two predominant landscapes of the St. Lawrence River watershed; an intensive farming landscape in the south shore lowlands and the forested landscape on the Canadian Shield on the north shore, respectively. In this study, a physically based hydrological model has been developed using the Cold Regions Hydrological Model (CRHM) for both of the catchments. The hydrological model outputs showed that we were able to simulate snow surveys and discharge measurements with a reasonable accuracy for both catchments. The acceptable performance of the model along with the strong physical basis of structure suggested that this model could be used for climate change sensitivity simulations. Based on the climate scenarios reviewed, a temperature increase up to 8°C and an increase in total precipitation up to 20% were analysed for both of the catchments. Both catchments were found to be sensitive to climate change, however the degree of sensitivity was found to be catchment specific. Snow processes in the Acadie River catchment were simulated to be more sensitive to warming than in the Montmorency River catchment. In case of 2°C warming, reduction in peak SWE was not be able to be compensated even by increased precipitation scenario. Given that, the Acadie River has already a mixed flow regime, even if 2°C warming is combined with an increase in precipitation, pluvial regime kept becoming more dominant, resulting in higher peaks of rain events. On the other hand, even 3°C of warming did not modify the flow regime of the Montmorency River. While there is shift towards earlier peak spring flows in both catchments, the shift was found to be more pronounced in the Acadie River. An earlier occurrence of snowmelt floods and an overall increase in winter streamflow during winter have been simulated for both catchments, which calls for renewed assessments of existing water supply and flood risk management strategies.
Keywords: Kinnard_Christophe

Can isolated and riparian wetlands mitigate the impact of climate change on watershed hydrology? A case study approach - Fossey, Maxime; Rousseau, Alain N. (Journal of Environmental Management, 2016)
The effects of wetlands on stream flows are well established, namely mitigating flow regimes through water storage and slow water release. However, their effectiveness in reducing flood peaks and sustaining low flows is mainly driven by climate conditions and wetland type with respect to their connectivity to the hydrographic network (i.e. isolated or riparian wetlands). While some studies have demonstrated these hydrological functions/services, few of them have focused on the benefits to the hydrological regimes and their evolution under climate change (CC) and, thus, some gaps persist. The objective of this study was to further advance our knowledge with that respect. The PHYSITEL/HYDROTEL modelling platform was used to assess current and future states of watershed hydrology of the Becancour and Yamaska watersheds, Quebec, Canada. Simulation results showed that CC will induce similar changes on mean seasonal flows, namely larger and earlier spring flows leading to decreases in summer and fall flows. These expected changes will have different effects on 20-year and 100-year peak flows with respect to the considered watershed. Nevertheless, conservation of current wetland states should: (i) for the Becancour watershed, mitigate the potential increase in 2-year, 20-year and 100-year peak flows; and (ii) for the Yamaska watershed, accentuate the potential decrease in the aforementioned indicators. However, any loss of existing wetlands would be detrimental for 7-day 2-year and 10-year as well as 30-day 5-year low flows.
Keywords: Rousseau_Alain

Adaptation des outils PHYSITEL/HYDROTEL au milieu boréal québécois : modélisation des processus hydrologiques et analyses de sensibilité et d’incertitudes. - Rousseau, Alain N.; Rousseau, A.N.; Mailhot, Alain; St-Hilaire, André (2015)
Les bassins versants du Moyen‐Nord quebecois (49e au 55e parallele) se distinguent par leur climatologie et le pourcentage eleve de territoires couverts par des lacs et milieux humides (de l’ordre de 20 a 30 %) et, surtout, par leur importante contribution a la production electrique du Quebec; le complexe de la riviere La Grande generant environ 40% de l’electricite quebecoise. Dans le contexte de la gestion de la production d’electricite, Hydro‐Quebec Production fait la prevision des apports aux reservoirs de ce complexe a l’aide d’un modele hydrologique global. Par ailleurs, depuis les annees 1980, le milieu boreal quebecois a subi des hausses de temperature et de precipitation qui ont modifie le regime des apports aux reservoirs. Compte tenu de ces changements et des caracteristiques physiographiques des bassins boreaux, il a ete propose d’utiliser un modele hydrologique distribue a base physique pour examiner l’impact sur ces apports des projections climatiques produites par Ouranos. En l’occurrence le modele HYDROTEL dont la prise en mains est en train d’etre completee par Hydro‐Quebec Production. Le modele qui est maintenant convenablement cale pour un certain nombre de bassins repond aux attentes dans les bassins du sud du Quebec. Toutefois, pour les grands bassins du Nord comme ceux du Complexe La Grande, l’utilisation du modele requiert des travaux d’adaptations, entre autres, aux niveaux de la modelisation des milieux humides et de la desagregation spatiale des precipitations simulees par les modeles climatiques. Les objectifs generaux de ce projet etaient d’accroitre notre comprehension de l’hydrologie du moyen nord afin qu’elle soit bien representee dans HYDROTEL tout en tenant compte des incertitudes parametriques associees aux differentes equations gouvernant les processus physiques. Ces objectives ont ete declines en trois activites de travail : (AT1) modelisation des processus hydrologiques; (AT2) calage et analyses de sensibilite, d’identifiabilite et d’incertitudes des parametres de calage d’HYDROTEL; et (AT3) amelioration des plateformes informatiques HYDROTEL et PHYSITEL, ce dernier etant un SIG dedie a la construction des bases de donnees de modeles hydrologiques distribues. Pour Ouranos et Hydro‐Quebec les principales realisations issues de ce projet incluent : (i) le developpement d’une methode eprouvee de desagregation sous grille de la precipitation mesoechelle permettant d’evaluer a fine echelle spatiale l’impact des changements climatiques sur les precipitations; (ii) une meilleure comprehension de la dynamique des ecoulements, du stockage de l’eau et de l’evapotranspiration d’un petit bassin versant boreal incluant une grande une tourbiere minerotrophe aqualysee; (iii) l’evaluation du parametrage de la sublimation et la relocalisation de la neige dues au vent et l’identification du besoin d’inclure le rayonnement sous la canopee pour bien reproduire la crue avec un modele complexe de l'evolution du couvert nival; (iv) la detection de la quasi neutralite frequente (~76% du temps, majoritairement le jour) de l’atmosphere au‐dessus d’un milieu humide causee par une turbulence mecanique forte et une grande inertie thermique; conditions ayant permises le developpement d’un modele simple d’evapotranspiration des milieux humides base le transfert massique et la stabilite atmospherique; (v) le developpement d’un modele de rayonnement net base uniquement sur des donnees de temperatures journalieres (min, max) et une estimation des parametres permettant de valider l’utilisation de l’equation de Penman‐Monteith dans le nord quebecois; (vi) la hierarchisation des parametres de calage d’HYDROTEL selon la saison et le developpement d’une methode permettant d’evaluer l’incertitude sur les debits simules et d’identifier son importance durant la fonte et l’etiage estival; (vii) dans un contexte d’analyse frequentielle des debits simules, evaluation de l’incertitude parametrique par rapport a l’incertitude statistique, cette derniere dominant pour les periodes de retour superieures a cinq ans; (viii) a l’aide de PHYSITEL, la premiere discretisation du complexe de la riviere La Grande (136 648 km2) en six sousbassins (LG1, LG2, LG3, LG4, La Forge 1 & 2,et Caniapiscau) leur subdivision en versants permettant le calcul de crues maximales probables a l’aide d’HYDROTEL; et (ix) le developpement d’une version 64 bits d’HYDROTEL incluant de nouveaux modules de de calculs de la temperature du sol et des bilans hydriques des milieux humides et isoles. L'avancement de nos comprehensions de l'hydrologie des milieux humides et du milieu boreal en general a ete a la base du developpement des versions adaptees d'HYDROTEL et de PHYSITEL qui permettront a Hydro‐Quebec d'apprehender, avec une modelisation distribuee, l'impact des changements climatiques sur le complexe de la riviere La Grande. Ces logiciels sont transposables a l’ensemble du milieu boreal canadien. Une entente conclut, depuis 2005, entre l’INRS et Hydro‐Quebec (HQ) permet d’ailleurs une distribution commerciale des differentes versions d’HYDROTEL avec interfaces usagers de meme qu’une distribution communautaire du noyau de calcul. Cette synergie a permis de mettre en commun des ressources et des expertises qui facilitent les echanges scientifiques et techniques entre les concepteurs d’HYDROTEL, le Centre d’expertise hydrique du Quebec (CEHQ), HQ, l’IREQ (Institut de recherche en electricite du Quebec) et d’autres usagers (ex. : l’IMTA, Instituto Mexicano de Technologia del Agua). Au total, plus d’une quarantaine de licences ont ete distribuees tant pour des besoins d’enseignement (Universite de Sherbrooke) et de recherche (Universite Laval, UQTR, UQAC, IREQ, Ecole de Technologie Superieure, INRA de Montpellier, Environnement Canada, Agriculture et Agroalimentaire Canada), que des besoins de prevision hydrologique (IMTA, Ville de Quebec, Centre d’expertise hydrique du Quebec, HQ). La modularite informatique d’HYDROTEL se prete egalement bien a cette synergie car elle offre la possibilite de partager le savoir‐faire et, par l’entremise d’un site internet public (CodePlex), de mettre a la disponibilite de tous les nouvelles versions du noyau de calcul. Ces developpements ont permis a l’equipe de l’INRS‐ETE d’acquerir une reconnaissance internationale en modelisation hydrologique distribuee. En effet, HYDROTEL et PHYSITEL ont dans le passe ete identifie comme les outils a utiliser dans le cadre d’appels de proposition de projets de determination du potentiel hydroelectrique finances par la Banque Mondiale [World Bank, 2009].
Keywords: Rousseau_Alain

Logistic models as a forecasting tool for snow avalanches in a cold maritime climate: northern Gaspésie, Québec, Canada - Gauthier, F.; Germain, Daniel; Hétu, Bernard (Natural Hazards, 2017)
Snow avalanches are a major natural hazard for road users and infrastructure in northern Gaspesie. Over the past 11 years, the occurrence of nearly 500 snow avalanches on the two major roads servicing the area was reported. No management program is currently operational. In this study, we analyze the weather patterns promoting snow avalanche initiation and use logistic regression (LR) to calculate the probability of avalanche occurrence on a daily basis. We then test the best LR models over the 2012–2013 season in an operational forecasting perspective: Each day, the probability of occurrence (0–100%) determined by the model was classified into five classes avalanche danger scale. Our results show that avalanche occurrence along the coast is best predicted by 2 days of accrued snowfall [in water equivalent (WE)], daily rainfall, and wind speed. In the valley, the most significant predictive variables are 3 days of accrued snowfall (WE), daily rainfall, and the preceding 2 days of thermal amplitude. The large scree slopes located along the coast and exposed to strong winds tend to be more reactive to direct snow accumulation than the inner-valley slopes. Therefore, the probability of avalanche occurrence increases rapidly during a snowfall. The slopes located in the valley are less responsive to snow loading. The LR models developed prove to be an efficient tool to forecast days with high levels of snow avalanche activity. Finally, we discuss how road maintenance managers can use this forecasting tool to improve decision making and risk rendering on a daily basis.

Ice-block fall and snow avalanche hazards in northern Gaspésie (eastern Canada): Triggering weather scenarios and process interactions - Graveline, Marie-Hélène; Germain, Daniel (Cold Regions Science and Technology, 2016)
Abstract The database of the Quebec Ministry of Transport allowed us to analyze the occurrence of ice-block falls and snow avalanches for the past decades along national road 132. The results show that ice structure collapse may be categorized into three distinct phases by using daily temperatures (minimum, maximum, and average) and the cumulative degree day (temperatures above 0°C) since the March 1 st , corresponding to the beginning of the ice wall melting period: 1) a short and intense period of ice-block falls from the mid-April to the beginning of May; 2) a period of constant activity, mainly during the two first weeks of May; and 3) isolated residual activity, with a low frequency of ice-block falls until the month of June. The snow avalanche days were mainly characterized by significant snowfalls or rain-on-snow events with temperature>0°C. The multi-hazard probability was then evaluated based on the timing and relative frequency of ice-block fall and the modeling of sufficient snowpack for avalanching. This simple method to assess the synergistic effect of hillslope processes allows a better understanding of the spring avalanche regime related to the collapse of ice structures. These findings are expected to assist in the management of natural hazards and to improve our knowledge of spatiotemporal dynamics of mass-wasting events on highways.